COMMUNICATION ETHIC IN SOCIAL MEDIA: Analitical Study of Surah Al-Hujarât - Khasanah, Faizatun (IAIN Tulungagung, 2019)
Commodification of religion in the social media public sphere is increasingly intense. This can be seen in the simultaneous election campaign that has justended. Political symbols are politicized and religious leaders have succeeded in shaping public opinion, especially on social media. As a result, social media has become an arena for discourse and rhetoric that no longer considers communication ethics. Using an philosophical approach, the paper examines ethical values on social media based on Surah al-Hujarât. The results of the analysis show that the value of communication ethics in Surah al-Hujarât involve two things: as a producer of news (communicator) and as a news reader (communicant). In Surah al-Hujarât explains that as a communicator in communicating must not demean others, does not contain elements of divideand rule, ghibah, namimah, hoax, and adjusted to the interlocutor. As communicants need to instill critical thoughts and tabayyun towards the truth of the news content.